Manifestações clínicas gastrointestinais e extraintestinais em crianças hospitalizadas em uma clínica infantil em belém, pará com viremia/rnaemia causada por norovírus - FARIAS, Fredison Pinheiro (2020)
Noroviruses (NoVs) are among the main causes of severe gastroenteritis (GE), belonging to the Caliciviridae family, and are divided into seven genogroups. The most frequent mechanism of transmission is via the fecal/oral and the symptoms are mainly diarrhea, vomiting, fever and abdominal pain, which can lead to acute dehydration and death. Studies already published have evidenced the presence of viremia/RNAemia caused by NoVs in patients with GE. The present study evaluated the severity of the manifestation of symptoms of severe GE by NoVs associated with the possible viremia/RNAemia caused by this agent in hospitalized children. A descriptive, cross-sectional, prospective and observational study of a hospital basis conducted at a children's hospital in Belém, Pará. Laboratory tests were performed at the Virology Section of the Evandro Chagas Institute for the study of NoVs in blood and faeces samples, where the fecal ELISA and the quantitative PCR method (RTPCR) were performed for analysis of serum samples. From March 2012 to June 2015, 3.740 patients were screened for the age group recommended by the study in two children's clinics in Belém (Pio XII Clinic and Pará Pediatric Clinic). A total of 600 children with severe GE were included, with 28 participants excluded, with 572 patients remaining. Among the 95 patients whose ELISA analysis detected the presence of NoVs in the faeces, 22,1% (21/95) of the patients were also positive in the serum. In countries that introduced the rotavirus vaccine, NoVs became the primary viral pathogen sought in pediatric patients with acute gastroenteritis. The presence of RNAemia occurs frequently among hospitalized children with severe GE caused by norovirus in Belém, Pará. The presence of RNAemia caused by norovirus was correlated with the higher number of episodes of vomiting per day in the patients, longer hospitalization, increase of severity by the Ruuska & Vesikari score, beside that, there was an increase in the number of leukocytes. Detection of norovirus RNA in faeces was superior to that found in serum/plasma. It was not possible to evaluate the correlation between exclusive breastfeeding and the severity of the clinical condition of GE caused by norovirus.